2018
DOI: 10.11152/mu-1687
|View full text |Cite
|
Sign up to set email alerts
|

Stitching of sensor-navigated 3D ultrasound datasets for the determination of large thyroid volumes – a phantom study

Abstract: Aims: Thyroid volume has to be measured in goiters prior to radioiodine treatment to calculate the needed amount of radioactivity. Modern clinical equipment for ultrasonography shows the trend to smaller probes, so that larger goiters do not fit any longer into the probe’s field of view. This study evaluated the feasibility and accuracy of stitching procedures applied to thyroid volumetric analysis performed using three-dimensional ultrasound (3D-US).Material and methods: Ad hoc thyroid phantoms of different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Stitching allows the generation of a jointed volume dataset out of several single US scans, leading to an EFOV. The introduced phantom study, using sensor-navigated (sn) US probes, confirmed the feasibility of the method even in large thyroid phantoms (up to 400 mL) [22].…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…Stitching allows the generation of a jointed volume dataset out of several single US scans, leading to an EFOV. The introduced phantom study, using sensor-navigated (sn) US probes, confirmed the feasibility of the method even in large thyroid phantoms (up to 400 mL) [22].…”
Section: Introductionmentioning
confidence: 54%
“…Therefore, the first purpose of the current study is to investigate whether stitching of two separately acquired 3D-US datasets of large volume thyroid phantoms (with several volume and shape variants) is feasible with ms US probes, too. The previous sn 3D-US study showed very high correlation coefficients between the measured and the reference volumes, revealing superior data for the mt method in comparison to the em approach [22]. Thus, the second aim of this study is to investigate whether similar results for volumetric analyses can be achieved with ms US probes.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations